A microalgal‐based preparation with synergistic cellulolytic and detoxifying action towards chemical‐treated lignocellulose. Issue 1 (2nd September 2020) - Benedetti, Manuel; Barera, Simone; Longoni, Paolo; Guardini, Zeno; Herrero Garcia, Natalia; Bolzonella, David; Lopez‐Arredondo, Damar; Herrera‐Estrella, Luis; Goldschmidt‐Clermont, Michel; Bassi, Roberto; Dall'Osto, Luca
Summary: High‐temperature bioconversion of lignocellulose into fermentable sugars has drawn attention for efficient production of renewable chemicals and biofuels, because competing microbial activities are inhibited at elevated temperatures and thermostable cell wall degrading enzymes are superior to mesophilic enzymes. Here, we report on the development of a platform to produce four different thermostable cell wall degrading enzymes in the chloroplast of Chlamydomonas reinhardtii . The enzyme blend was composed of the cellobiohydrolase CBM3GH5 from C . saccharolyticus, the β‐glucosidase celB from P . furiosus, the endoglucanase B and the endoxylanase XynA from T . neapolitana . In addition, transplastomic microalgae were engineered for the expression of phosphite dehydrogenase D from Pseudomonas stutzeri, allowing for growth in non‐axenic media by selective phosphite nutrition. The cellulolytic blend composed of the glycoside hydrolase (GH) domain GH12/GH5/GH1 allowed the conversion of alkaline‐treated lignocellulose into glucose with efficiencies ranging from 14% to 17% upon 48h of reaction and an enzyme loading of 0.05% (w/w). Hydrolysates from treated cellulosic materials with extracts of transgenic microalgae boosted both the biogas production by methanogenic bacteria and the mixotrophic growth of the oleaginous microalga Chlorella vulgaris . Notably, microalgal treatment suppressed the detrimental effect of inhibitory by‐products released from the alkaline treatment of biomass, thus allowing for efficient assimilation of lignocellulose‐derived sugars by C . vulgaris under mixotrophic growth.